2008
DOI: 10.1016/j.bcp.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

PCNA damage caused by antineoplastic drugs

Abstract: Structurally diverse chemotherapeutic and chemopreventive drugs, including camptothecin, doxorubicin, sanguinarine, and others, were found to cause covalent crosslinking of proliferating cell nuclear antigen (PCNA) trimers in mammalian cells exposed to fluorescent light. This PCNA damage was caused by both nuclear and cytoplasmically localizing drugs. For some drugs, the PCNA crosslinking was evident even with very brief exposures to laboratory room lighting. In the absence of drugs, there was no detectable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 85 publications
0
27
0
Order By: Relevance
“…Because photosensitization by UVA is known to generate mainly 1 O 2 [4], we examined its implication in hXRCC3 oxidation by irradiating CHO cells in the presence of increasing concentrations of NaN 3 (Figure 5A) or L-Histidine (Figure 5B), two quenchers of 1 O 2 [40], [41], or of N-acetyl-L-cysteine (NAC) (Figure 5C) that scavenges free radicals [42]. Following quantifications, we found that hXRCC3 oxidation by UVA radiation was significantly prevented by increasing the concentration of NaN 3 or L-Histidine but not of NAC (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…Because photosensitization by UVA is known to generate mainly 1 O 2 [4], we examined its implication in hXRCC3 oxidation by irradiating CHO cells in the presence of increasing concentrations of NaN 3 (Figure 5A) or L-Histidine (Figure 5B), two quenchers of 1 O 2 [40], [41], or of N-acetyl-L-cysteine (NAC) (Figure 5C) that scavenges free radicals [42]. Following quantifications, we found that hXRCC3 oxidation by UVA radiation was significantly prevented by increasing the concentration of NaN 3 or L-Histidine but not of NAC (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of CV-1 mammalian cells with Nic-Cl (1mM) induced a high molecular weight PCNA antibody-reactive band migrating at 93 kDa. This is the well-established molecular weight of the covalently crosslinked PCNA trimer [41]. The formation of the PCNA trimer was robust as detected by Western blotting (Fig 2 a) and was found to be dose-dependent (Fig 3 a).…”
Section: Resultsmentioning
confidence: 58%
“…Covalent crosslinking of PCNA subunit, thus, interferes with PCNA ring opening and, consequently, with its function. Crosslinking of PCNA subunits is thus considered as a critical damage to PCNA [27, 41]. Because PCNA is a nuclear protein, PCNA crosslinking has been used as a sensitive marker for intracellular protein damage induced by different cytotoxic compounds [27, 41].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations